Level-dependent volatility in jumping short-rate models - Chitambo, Nigel Elton Nyasha (Department of Finance and Tax, 2025)
This dissertation constructs a no-arbitrage term structure with deterministically timed randomly sized jumps to price interest rate contingent claims while accounting for level-dependent volatility. This dissertation will price such claims using an implicit finite difference scheme to implement a modelling framework that prices bonds, bond options and caplets with scheduled shocks to the short-term interest rate to simulate macroeconomic announcements and other sudden developments. This dissertation found that the prices derived from the implicit finite difference scheme agree with those derived from Monte-Carlo simulations and, where applicable, analytical solutions. Moreover, this dissertation shows how innovations in the short-term rate affect the valuations of interest rate contingent claims.